Barriers and facilitators to primary care research: views of GP trainees and trainers. Issue 2 (2022) - Stephenson, Sarah; Allan, Hilary; Hesselgreaves, Hannah; Rouse, John; Tang, Eugene; Burton, Morag; Tang, Eugene; Wroe, Caroline; Williams, Penny; Bellamy, Richard
No abstract available